Pengaruh Brand Community Wardah Youth Ambassador Terhadap Brand Trust Wardah - Syahwitri, Sylviana Suci; Dianita, Indria Angga (eProceedings of Management, 2024)
One form of marketing communication that is widely used by companies is building a brand community as a marketingcommunication strategy to sell their products. A brand community is a specific community but not geographicallybound, based on structured social relationships between brand admirers. As with other communities, brandcommunity have three indicators that form a recognizable community, including consciousness of kind, rituals andtraditions, and moral responsibility. This research was conducted with the aim of measuring the magnitude of theinfluence of the Wardah Youth Ambassador brand community on Wardah's brand trust. Meanwhile, brand trust is thewillingness of consumers to rely on consumers' abilities to carry out brand functions. In this study, researchers usedthe S-O-R (Stimulus-Organism-Response) theory to measure how much influence the Wardah Youth Ambassadorbrand community has on consumers' Wardah brand trust. The method used in this research is using a quantitativeapproach with data collection techniques using online questionnaires from 384 respondents. The results of theresearch conducted by this researcher explain that the Wardah Youth Ambassador brand community has an influenceon 56.3% of Wardah's brand trust, while 43.7% is influenced by other variables not discussed in this research. Keywords-brand community, brand trust, Wardah Youth ambassador, Wardah